The Transparency Paradox In Digital Employee - Ahmad Nur Sholikin; Fahrul Ismaeni (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2025)
This study examines the paradoxical finding that transparency in digital HR systems may be more important than processing efficiency for employee satisfaction, challenging the dominant efficiency paradigm in digital transformation literature. Drawing on organizational justice theory and administrative burden theory, we investigate how transparency features in a frugal digital innovation enhance employee satisfaction through informational justice and perceived organizational support in a bureaucracy-heavy university context. We employed a mixed-methods research design to evaluate a Google Workspace-based international travel approval system at a major Indonesian research university. Quantitative data were collected from 100 faculty members and administrators, and qualitative data were gathered through open-ended responses. Results reveal a striking transparency paradox: despite moderate processing efficiency, the system achieved high overall satisfaction (87%). Transparency emerged as the highest-rated dimension (M=4.084), while process efficiency remains a moderately important factor (r=0.524, p